Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios: are they useful for predicting gestational diabetes mellitus during pregnancy? - Sargın MA; Yassa M; Taymur BD; Celik A; Ergun E; Tug N (Dove Medical Press, 2016)
Mehmet Akif Sargın, Murat Yassa, Bilge Dogan Taymur, Ayhan Celik, Emrah Ergun, Niyazi Tug Department of Obstetrics and Gynecology, Fatih Sultan Mehmet Research and Training Hospital, Istanbul, Turkey Objective: We aimed to investigate whether the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) could be utilized to screen for gestational diabetes mellitus (GDM).Subjects and methods: NLR and PLR were assessed by retrospective analysis of 762 healthy and pregnant women with GDM. The patients were stratified into four groups, as follows: GDM (n=144), impaired glucose tolerance (n=76), only screen positive (n=238), and control (n=304).Results: The leukocyte, neutrophil, and lymphocyte counts were significantly higher in the study groups compared with the control group (P=0.001; P<0.01). There were no statistically significant differences between the groups with respect to the NLR and PLR (P>0.05).Conclusion: We do not recommend that blood NLR and PLR can be used to screen for GDM. However, increase in the leukocyte count is an important marker for GDM as it provides evidence of subclinical inflammation. Keywords: inflammation, lymphocytes, neutrophils, platelets, pregnancy